The influence of media implementation of Algebra Cartoon Books on the learning outcomes of class VII students at Junior High School Plus Darus Sholah Jember - Azizah, Siti Nur; Anas, Aswar; Sujiwo, Dimas Anditha Cahyo (SAINTIS Publishing, 2023)
Learning media is anything that can convey and channel messages from sources in a planned manner so as to create a conducive learning environment where recipients can carry out the learning process efficiently and effectively. This research is aimed at finding out the effect of implementing algebra cartoon books on the learning outcomes of class VII students at SMP Plus Darus Sholah Jember in the 2023–2024 academic year. The method used is the quasi-experiment research method with a posttest-only control design research design. The population of this study was all in class VII of SMP Plus Dasrus Sholah Jember, for a total of 76. Meanwhile, the sample used was class VIIA, with a sample of 15 people from the experimental class and 15 people from class VIIB as the control class. The sample data collection technique was carried out by random sampling. This research process shows that the implementation of algebra cartoon book media on the learning outcomes of class VII students at SMP Plus Darus Sholah Jember was carried out by dividing class VII into two groups, namely the experimental class, which used algebra cartoon book media, and the control class, which used conventional learning methods. The data analysis technique used is the independent sample t-test. The results of the research show that the significance value (2-tailed) is 0.000, which is lower than the significance level of 0.05. Thus, it can be concluded that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. In simple terms, it can be stated that there is a positive influence from the use of the Algebra Cartoon Book on the learning outcomes of class VII students in the mathematics subject algebra material at SMP Plus Darus Sholah Jember.